A multi-input single-output Dickson-type AC/DC converter for vibration energy harvesting - Kei Eguchi (Elsevier, 2021)
To achieve efficient vibration energy harvesting, we propose a new inductor-less ac/dc converter with multiple-input single-output (MISO) structure in this paper. Unlike existing ac/dc converters with single-input single-output (SISO) structure, the proposed inductor-less ac/dc converter achieves a high voltage gain and small size by the MISO structure employing Dickson-type converters. The properties of the proposed inductor-less MISO converter are evaluated by theoretical analysis and computer simulations. For the proposed converter with two modules, the simulation results demonstrate that the voltage gain and power efficiency reach about 6.7 and 84% at 500 mW, respectively, for 3.5 V inputs at 50 kHz. Furthermore, the validity of the circuit design is confirmed experimentally by some breadboard tests.